2018
DOI: 10.1039/c8qo00496j
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic enantioselective α-sulfenylation of β-ketocarbonyls by chiral primary amines

Abstract: A simple chiral primary amine catalyst was identified to enable effective catalysis in direct α-sulfenylation of acyclic and cyclic β-ketocarbonyls with good yields and excellent enantioselectivities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…Recently, we developed the chiral primary− tertiary diamine catalyzed sulfuration reaction of ketones. 18 Survey of the catalysts showed significant dependence on the size of the N-substituents (see the SI). Regression analysis also showed that the enantiocontrol was mainly determined by the outsphere B1 and innersphere B 1 ′ (Scheme 4, eq 7, and Figure S4B).…”
Section: Organic Lettersmentioning
confidence: 99%
“…Recently, we developed the chiral primary− tertiary diamine catalyzed sulfuration reaction of ketones. 18 Survey of the catalysts showed significant dependence on the size of the N-substituents (see the SI). Regression analysis also showed that the enantiocontrol was mainly determined by the outsphere B1 and innersphere B 1 ′ (Scheme 4, eq 7, and Figure S4B).…”
Section: Organic Lettersmentioning
confidence: 99%
“…reported the KI‐catalyzed oxidative sulfenylation of 375 to 376 with aryl thiols by using oxygen as the green oxidant (Scheme 75). [170] In 2018, Luo and co‐workers identified a simple chiral amine 379 to catalyze the enantioselective α ‐sulfenylation of β ‐dicarbonyls with N ‐phenylthio phthalimide 378 [171] . The α ‐methyl β ‐keto amide 377 was converted to the α ‐sulfenylation product 380 in 99 % yield and 45 % ee (Scheme 76).…”
Section: Reactivities Of β‐Keto Amidesmentioning
confidence: 99%
“…Asymmetric α‐sulfenylation of acyclic and cyclic β‐ketocarbonyls 188 were developed by Mi and co‐workers, providing corresponding products in ideal results (Scheme 62). [64] The Bronsted acid acted as a liaison throughout the reaction, which could promote the isomer conversion of enamine and iminium. The whole reaction process was performed by forming enamine/iminium intermediates.…”
Section: Sulfenylation Reactionsmentioning
confidence: 99%